A progressividade nos impostos (os princípios da igualdade e da capacidade contributiva) (perfil constitucional) - Malheiros, Carolina Rocha (2014)
The present work aims to study the progressive taxation on the Brazilian Statutory Law and it will be treated under the focus of the Brazilian Federal Constitution of 1988. The progressivity applied in taxes is an issue that demands the study of the Brazilian Constitutional System, integrated by principles, which are rules of the highest hierarchy guiding the application of the other rules within the legal system. There are several constitutional principles that inform the legal system and guide the taxation. Due to the specificity of each principle and seeking the best understanding of the proposed issue, we believe that the principles of equality and ability to pay, which more closely rules the progressivity of taxes, deserve a special highlight. In order to achieve such objective, it is necessary to analyze the principle of ability to pay (contained in the principle of equality), which requires all taxpayers, via tax payment, to contribute to the extent of their outward manifestations of wealth. For this purpose, we have investigated the criteria for the assessment and effective application of the principle of ability to pay in taxes. In view of these elements, being the progressivity the vector for the exercise of a fair and equitable taxation in tax matters, we will implement our studies on progressivity with tax purpose (arising from the principle of ability to pay) and extra fiscal. Thus, once analyzed all the criteria that the subject requires, the result to be achieved is the application of progressive taxation in each of the taxes set forth on articles 153 to 156 of the Brazilian Federal Constitution of 1988